Incorporation of interface current method based on 2D CP approach in VISWAM code system for hexagonal geometry. (June 2016) - Khan, Suhail Ahmad; Mathur, Arvind; Jagannathan, V.
Highlights: Development of lattice code VISWAM. Implementation of interface current method based on 2D Collision Probability Technique. Using double P2 expansion of angular flux in hexagonal geometry. Modeling Fuel Assembly geometry exactly. Analysis of HTTR Fuel Assembly Benchmark. Abstract: The design and operation of nuclear power reactors has seen a significant improvement since the operation of the first reactor in 1950s. Most of the operating reactors around the world today belong to the Generation II or III design versions. Generation IV reactors which are being evolved, have improved thermal efficiencies. Very High Temperature Reactor (VHTR) is one of the reactor concepts being considered under the scope of Generation IV reactors. The development of next generation reactors requires advanced reactor physics methods with greater accuracy and fidelity than traditional diffusion methods. A comprehensive code system VISWAM for physics analysis of current and future power reactors is being developed (Jagannathan et al., 2013a). The lattice analysis method initially incorporated in VISWAM code is based on a combination of 1D multigroup transport and a 2D few group diffusion theory. This methodology is computational efficient. However for analyzing problems with complexities like Gd or control cells some limitations were noted (Jagannathan et al., 2013b). We have applied the 2D collision probability (CP) method at single pincell level and linked the cells using interface currents with double P2 (DP2) expansion of angular flux at cell boundaries. We have implemented this method in VISWAM to analyze hexagonal fuel assembly (FA). The use of DP2 expansion for hexagonal geometry is not reported in the literature to the best knowledge of the authors. The FA cell in hexagonal geometry with irregular lattice structure at boundaries is modeled exactly. Two benchmark problems, a heterogeneous benchmark problem that is typical of a high temperature reactor (HTTR) proposed by Zhang et al. (2011) and VVER – 1000 OECD computational benchmark (NEA/NSC/DOC, 2002), are studied using VISWAM. The present paper describes the advanced methodology incorporated in VISWAM and the comparison of results of benchmark analysis with published results. The k∞ for HTTR pincell/FA calculation matches within 0.01%/0.18% respectively with the benchmark results. The RMS error in the fission density distribution is seen as 0.13%. For VVER – 1000 OECD benchmark, the k∞ compares well with benchmark results. The % RMS deviation in fission densities using DP2 is seen to be 0.462%.